Microwave-Assisted, [Bmim]PF6-Catalyzed Synthesis of Benzoxazoles Under Solvent-free Conditions - Duc, Dau X. (Current Organocatalysis, 2023)
Background: An efficient and green strategy for the synthesis of 2-arylbenzoxazoles using [Bmim]PF6 ionic liquid as a catalyst has been investigated via the condensation of oaminophenol with aldehydes. The microwave-assisted synthesis features some advantages such as good yield of products, broad substrate scope, short reaction time, and absence of metal catalyst and solvent. Furthermore, the synthesis could be conveniently expanded to a gram scale. Methods: 2-arylbenzoxazoles were obtained from o-aminophenol with aldehydes using [Bmim]PF6 ionic liquid as a catalyst under microwave irradiation at 80ºC, 120 W. Results: Twenty-three 2-arylbenzoxazole derivatives were furnished in good to excellent yields under optimized conditions. The structures of these compounds were confirmed by analysis of NMR data. In addition, the method could be conveniently expanded to gram scale. Conclusion: An efficient and straightforward protocol for the synthesis of 2-arylbenzoxazoles catalyzed by [Bmim]PF6 ionic liquid has been demonstrated. The synthesis delivers several advantages such as short reaction time, broad substrate scope, scalability, solvent-free conditions, and high efficiency. The reaction mechanism and applications of this synthesis are currently ongoing in our lab and will be reported in due course.
Keywords: benzadehyde